How you ask really matters: randomised comparison of four sexual behaviour questionnaire delivery modes in Zimbabwean youth. Issue 2 (13th October 2010) - Langhaug, Lisa F; Cheung, Yin Bun; Pascoe, Sophie J S; Chirawu, Petronella; Woelk, Godfrey; Hayes, Richard J; Cowan, Frances M
Abstract : Objective: A sexual health survey among rural Zimbabwean youth was used to compare the validity and reliability of sexual behaviour measures between four questionnaire delivery modes. Methods: Using a random permuted block design, 1495 youth were randomised to one of four questionnaire delivery modes: self-administered questionnaire (SAQ=373); SAQ accompanied by an audio soundtrack (Audio-SAQ=376); face-to-face interview with sensitive questions placed in a confidential voting box (Informal confidential voting interview; ICVI=365); and audio computer-assisted survey instrument (ACASI=381). Key questions were selected a priori to compare item non-response and rates of reporting of sensitive behaviours between questionnaire delivery modes. Qualitative data were collected on perceived method acceptability (n=115). Results: Item non-response was significantly higher with SAQ and Audio-SAQ than with ICVI and ACASI (p<0.001). After adjusting for covariates, the odds of reporting sexual activity among Audio-SAQ and ACASI users were twice as high as the odds for SAQ users (Audio-SAQ AOR=2.05 (95% CI 1.2 to 3.4); ACASI AOR=2.0 (95% CI 1.2 to 3.2)), with no evidence of reporting difference between ICVI and SAQ users (ICVI AOR=1.0 (95% CI 0.6 to 1.8)). ACASI users reported a lower age at first intercourse and were more likely to report a greater number of partners (mean difference=1.06; 95% CI 0.33 to 1.78; p=0.004). They reported an increased ability to answer questions honestly (p=0.004) and believed their answers would be kept secret. Participants claimed increased comprehension when hearing questions while reading them. ICVI users expressed difficulty answering sensitive questions, despite understanding that their answers were unknown to the interviewer. Conclusion: ACASI appears to reduce bias significantly, and is feasible and acceptable in resource-poor settings with low computer literacy. Its increased use would likely improve the quality of questionnaire data in general and sexual behaviour data specifically.